Case report: Ketogenic diet acutely improves cognitive function in patient with Down syndrome and Alzheimer’s disease - Bosworth, Annette; Loh, Vyvyane; Stranahan, Blackjack N.; Palmer, Christopher M. (Frontiers in Psychiatry, 2023)
The therapeutic use of ketogenic diets began in the 1920s to treat intractable epilepsy. Since then, there has been renewed interest in nutritional approaches to neurodegenerative diseases such as Alzheimer’s Disease (AD) and Parkinson’s Disease. While multifactorial in etiology, AD has been well-associated with glucose hypometabolism measured with FDG-PET. It has been hypothesized that providing ketone bodies as an alternate fuel source to the brain may ‘rescue’ neurons from cell death and thus ameliorate cognitive decline. We present a case report of a patient with Downs Syndrome (DS) and absence seizures with accelerated cognitive decline over 6 years who reversed her disease progression over 6 weeks (ADCS-ADL score of 34 to 58) on a ketogenic diet. She tolerated the diet well without complications. The therapeutic use of a ketogenic diet was associated with significant cognitive improvement in this patient with concurrent DS and dementia.